Penyusunan modul fotogrametri digital pada perangkat lunak pengolahan citra PCI Easi/Pace - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
In the late of 1980's photogrammetry entered a new stage of development, which is digital or soficopy photogrammetry. Consequently there is a demand for software package to perform all photogrammetry tasks in computer workstations. This paper addresses the development of digital photogrammetric operations in the PCI EASI/P ACE image analysis system. The performance of the development software was evaluated in term of the accuracy, the flexibility and the future developments.